Bridging epigenetics and metabolism: Role of non-essential amino acids - Phang, James M. (Landes Bioscience, 2013)
Recent research suggests that chromatin-modifying enzymes are metabolic sensors regulating gene expression. Epigenetics is linked to metabolomics in response to the cellular microenvironment. Specific metabolites involved in this sensing mechanism include S-adenosylmethionine, acetyl-CoA, alphaketoglutarate and NAD(+). Although the core metabolic pathways involving glucose have been emphasized as the source of these metabolites, the reprogramming of pathways involving non-essential amino acids may also play an important role, especially in cancer. Examples include metabolic pathways for glutamine, serine and glycine. The coupling of these pathways to the intermediates affecting epigenetic regulation occurs by “parametabolic” mechanisms. The metabolism of proline may play a special role in this parametabolic linkage between metabolism and epigenetics. Both proline degradation and biosynthesis are robustly affected by oncogenes or suppressor genes, and they can modulate intermediates involved in epigenetic regulation. A number of mechanisms in a variety of animal species have been described by our laboratory and by others. The challenge we now face is to identify the specific chromatin-modifying enzymes involved in coupling of proline metabolism to altered reprogramming of gene expression.